EFFORTS TO INCREASE STUDENTS LEARNING OUTCOMES ON FRACTION MATERIALS WITH CONTEXTUAL TEACHING AND LEARNING MODEL - Lois Juvita Anggelika Borusilaban; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Learning activities with this contextual teaching and learning model are learning that connects students with the real world. The purpose of this classroom action research is to find out the improvement of student learning outcomes in grade 2 SDN 1 Tebluru on fractions by using the contextual teaching and learning model. This research uses data collection techniques in the form of observation, interviews, tests, and documentation. After that the data collected will be analyzed using quantitative qualitative data analysis techniques. The results of this study indicate an increase in student learning outcomes in each cycle. In terms of the average learning outcomes from pre-cycle to cycle II, the scores were 65.7 to 84.3 and increased again to 88.6. In terms of the percentage of the number of students who completed, there was also an increase from 28.5% in the pre-cycle, to 71.4% in the first cycle, and 85.6% in the second cycle. Based on the results of the study, it can be concluded that the application of the contextual teaching and learning learning model in improving the learning outcomes of second grade students at SD N 1 Tebluru in learning mathematics with simple fractions